The impact of DNA sequencing technology on agriculture - Pearl, Stephanie (Henry Stewart Talks, 2014)
Genomics and the world’s most important crops, Traditional breeding and limitations, Domestication bottleneck, Genomics-assisted breeding, Conducting a sequencing project, Sample preparation, Library preparation, Reduced representation sequencing, Multiple sequencing technology options, Data processing, Post-processing, Genotyping platforms, Applications of the data, Understanding genetic architecture, Mapping the genome, QTL mapping, Genome-wide association mapping, From QTL to candidate gene, Alternative to MAS, Keys to success for accelerated crop breeding, Hot areas for the future of breeding, Advancement of underutilized crops, Improving global food security